Empowering Through Psychodrama: A Qualitative Study at Domestic Violence Shelters - Ron, Yiftach; Yanai, Liat (Frontiers in Psychology, 2021)
Psychodrama is a therapeutic method in which the stage is used to enact and reenact life events with the aim of instilling, among other positive changes, hope and empowerment in a wide range of populations suffering from psychological duress. The therapeutic process in psychodrama moves away from the classic treatment of the individual in isolation to treatment of the individual in the context of a group. In domestic violence situations, in which abusive men seek to socially isolate their victims from family and friends, the social support that psychodrama provides can positively influence the psychological health and well-being of the participants. This qualitative study examines the manner in which psychodramatic treatment can empower abused women residing in domestic violence shelters and help them regain control of their lives. An action research study of domestic violence survivors living in a women's shelter in Israel, over a 12-month period, demonstrates the role of psychodrama therapy in promoting the reduction of anxiety, stress, guilt, and self-blame, while reinforcing perceptions of self-worth and confidence. These findings contribute to our understanding of the potential of psychodrama in helping reshape life roles and reframe experiences within a creative process, with the aim of facilitating a transition from powerlessness to powerfulness among vulnerable populations.